2000
DOI: 10.1007/s001090000170
|View full text |Cite
|
Sign up to set email alerts
|

Detection of thyroid-stimulating hormone receptor and Gs α mutations: in 75 toxic thyroid nodules by denaturing gradient gel electrophoresis

Abstract: The actual frequency of constitutively activating thyrotropin receptor or Gsalpha mutations in toxic thyroid nodules (TTNs) remains controversial as considerable variation in the prevalence of these mutations has been reported. We studied a series of 75 consecutive TTNs and performed mutation screening by the more sensitive method of denaturing gradient gel electrophoresis (DGGE) in addition to direct sequencing. Furthermore, the likelihood of somatic mutations occurring in genes other than that for the thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
101
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 38 publications
9
101
1
3
Order By: Relevance
“…The frequency of these mutations varies among reports but amounts to 50-80% [19][20][21]. In contrast, it has been reported to be very low in Japan [23].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The frequency of these mutations varies among reports but amounts to 50-80% [19][20][21]. In contrast, it has been reported to be very low in Japan [23].…”
Section: Discussionmentioning
confidence: 98%
“…Vanvooren et al consistently identified four mutations in the TSHR gene in 10 Japanese AFTN patients and thus suggested that activating mutations in the TSHR gene may not be rare in the Japanese population [18]. In contrast to the TSHR gene, the incidence of the mutations in Gsα is reportedly low in Europe as well as in Japan [18][19][20]22]. In the present report, we tested whether our patient harbored the mutations in exons 9 and 10 of the TSHR gene and those in exons 8 and 9 of the Gsα gene, in which the known hot spots for mutations exist [19,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations